Protection against Toxoplasma gondii cysts in pigs immunized with rROP2 plus Iscomatrix - Ivo Alexandre Leme da Cunha; Dauton Luiz Zulpo; Alexandra Taroda; Luiz Daniel de Barros; Jonatas Campos de Almeida; Sérgio Tosi Candim; Italmar Teodorico Navarro; João Luis Garcia (Revista Brasileira de Parasitologia Veterinária, 2020)
Abstract This study aimed to evaluate the humoral immune response in pigs immunized intranasally and intramuscularly with recombinant Toxoplasma gondii rROP2 protein in combination with the adjuvant Iscomatrix. Twelve mixed breed pigs divided into three groups (n=4) were used, G1 received recombinant ROP2 proteins (200 µg/dose) plus Iscomatrix, G2 received PBS plus Iscomatrix, and G3 as the control group. The intranasal (IN) and intramuscular (IM) routes were used. Animals were challenged orally with VEG strain oocysts and treated on day three after challenge. Fever, anorexia, and prostration were the clinical signs observed in all animals. All the G1 animals produced antibodies above the cut-off on the day of the challenge, while the G2 and G3 remained below the cut-off. Better partial protection against parasitemia and cyst tissue formation was observed in G1 than G3. The protection factors against tissue cyst formation were 40.0% and 6.1% for G1 and G2, respectively, compared to G3. In conclusion, there were not systemic antibody responses in pigs with IN immunization with rROP2+Iscomatrix; however, after IM immunization, those animals produced higher titers than animal controls. We associated these results with partial protection obtained against parasitemia and tissue cysts formation.